Organizational communication factors in Turkish companies exporting to transition countries - Agun, Gaye Berna (My University, 1999)
GEÇİŞ EKONOMİLERİNE İHRACAT YAPAN TÜRK FİRMALARINDA ORGANİZASYON İÇİ İLETİŞİM FAKTÖRLERİ ÖZET Organizasyoniçi iletişim; semboller yardımıyla bir organizasyon üyesinden çıkan bilginin diğer organizasyon üyesine iletilmesi ve onun tarafndan algılanmasıdır. İş ortamının en önemli ve hayatsal fonksiyonlarndan biridir organizasyon içi iletişim. Bu tezin amacı organizasyon içindeki iletişim faktörlerini belirlemektir. Bu nedenle , tez de ilk bölümde genelden özele giden konuyla ilgili literatür taraması, tanımlar, konsept, teoriler, fonksiyonlar, organizasyon içi iletişimin çeşitleri, yönleri araştırılmıştır. Tezin ikinci bölümünde, geçiş ekonomileri araştırılmış, geçiş ekonomisi konusu tanımlandıktan sonra bu tür ekonomileri yaşayan ülkeler saptanmış, genel ekonomik yapıları, coğrafyalarına göre gruplandırılmaları incelenmiştir. Türkiyenin de gelişen büyük bir pazar olarak ve geçiş ekonomilerine ihracat yapan bir ülke olarak genel ekonomisi araştırılmış, geçiş ekonomilerine ihracat yaparak kendi ekonomisine de faydalar sağlayacağı savunulmuştur. Saha araştırması, anketleri geçiş ekonomilerine ihracat yapan Tük firmalarında yaplmaya karar verilmiş, bu firmaları belirlemek için, İstanbul Sanayi Odası' na hazırlanılan ülke listesi verilmiş, ve bu ülkelere ihracat yapan ISO üyesi Türk firmaları örneklem olarak belirlenmiştir. Ancak listedeki firma sayısı çok fazla olduğundan bu listeden tesadüfi örneklemeyle seçilen 20 firmaya hazırlanılan anketler dağıtılmış, her firmadan beş adet olmak üzere toplam 100 adet anket elde edilmiş ve istatistiki metod olarak faktör analizi uygulanmıştır. Tezin üçüncü ve son bölümü olan bulgular ve sonuç kısmında; faktör analizi sonucunda belirlenen 12 adet organizasyoniçi iletişim faktörü belirtilmiş, ayrca bulunan faktörler hakkında ankletlerde kullanılan demografiklerde anlamlı bir farklılık olup olmadığı varyans analizi metoduyla araştırılmış ve sonuçları belirtilmiştir. ORGANIZATIONAL COMMUNICATION FACTORS IN TURKISH COMPANIES EXPORTING TO TRANSITON COUNTRIES

Communication in the organizations is; the transmitting of information and understanding by one organization member to another through the use of symbols. It is one of the most important and vital function in a job environment. The aim of the thesis is to define communication factors in an organization. Therefore in this thesis, for the first part of the literature survey; going from general to specific; the definition, the concept, the theories, the functions, the forms and the movement of organizational communication is studied. The second part of the literature survey studies the concept of the transition economies. After defining the term of transition economy, the transition countries related to that definition are listed. Their economic characteristics and status' are generally studied. Turkey's status as a big emerging market country is also analyzed, and Turkey's economic opportunities related to transition countries overviewed. For the field research; it is decided to conduct the questionnaires that are designed to define organizational communication factors, at the Turkish companies which are exporting to transition countries. Since the research field is so broad; the narrow the sample size; from the maintained ISO (İstanbul Chamber of Commerce) list; some Turkish firms in İstanbul that are exporting to transition countries are chosen as sample. First an open-ended questionnaire is given to 30 employees at different levels in 7 companies. From the answers given and the from the theory table; variables for the pre-test are obtained. Pre-test also conducted 30 employees in 7 different companies and factor analysis is conducted. Finally the questionnaires are given to 20 Turkish companies (5 to each of them) from the obtained ISO list, and collected 100 back. The answers are analyzed with statistical tools; first factor analysis and then One- Way Anova; to define the significant differences between the factors and demographic variables asked. Findings and the comments are listed at the last part of the thesis. It is observed that most of the employees working at the sample firms, do not have the necessary knowledge about organizational communication and a proper communication training might be useful. While preparing a training course about organizational communication to the firms that are exporting to transition countries specially, the status of significant differences found out at the end of the analysis assumed to be very useful.
Keywords: KAMU YÖNETİMİ